How prepared are Myanmar's health care professionals in their response to gender-based violence? - Aye Nyein Ei; Montakarn Chuemchit (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - Gender-based violence (GBV) has negative impact on the health and well-being of the survivors. The initial response can lessen the magnitude of the effect, and thus the health care sector's readiness to respond to GBV cases is important. This study aimed to explore the knowledge, attitude and its association to practice regarding GBV response among health care personnel. Design/methodology/approach - A cross-sectional study was conducted in 48 public hospitals in Yangon, Myanmar, involving 398 participants including doctors and nurses, by a self-administered structured questionnaire. Findings - Among 398 participants, most of the participants had moderate level of knowledge, attitude and supportive environmental factors. Only 12.8% had experienced GBV management. The respondents with a bachelor's degree were more likely to practice on health care management towards GBV cases than those who finished with a diploma degree. The medical officers and senior medical officers were more likely to practice than the junior nurses. The participants who had already attended the trainings had more practice than those who had not. Those who work in the regional hospitals were less likely to practice than those who work in the station-level hospital. Originality/value - This paper explored the associated factors to health care personnel's practice of health care management towards GBV survivors in Myanmar which contains information about knowledge, attitude and supportive environmental factors. The study results can be used for a supportive data for health system strengthening the response of GBV cases in Myanmar.